Probabilistic reliability analysis of Red river dike system protecting Giao Thuy - Nam Dinh :Master thesis Major Sustainble Hydraulic Structures Coastal Engineering and Management: Code 62-58-02-03 - Phạm, Viết Đỉnh (Trường Đại học Thủy Lợi, 2020)
This Master programme is supported by NICHE - VNM 106 Project